(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
This article examines the growing role of personalization technologies in digital marketing, focusing specifically on how user behavior is tracked, interpreted, and transformed into adaptive marketing experiences. As digital ecosystems evolve into data-intensive environments, companies increasingly rely on behavioral analytics to refine customer journeys, predict preferences, and deliver hyper-relevant content. By analyzing scholarly research in consumer psychology, data science, marketing analytics, and information systems, the study reveals how personalization contributes to value creation by enhancing relevance, reducing search friction, and strengthening emotional engagement. At the same time, it highlights critical tensions surrounding privacy, algorithmic opacity, and the risk of behavioral over-targeting. The findings emphasize that personalization, when executed responsibly, significantly improves marketing effectiveness, yet requires balanced governance, ethical safeguards, and transparent data practices.